2007
DOI: 10.1029/2007jd008787
|View full text |Cite
|
Sign up to set email alerts
|

Ozone columns obtained by ground‐based remote sensing in Kiev for Aura Ozone Measuring Instrument validation

Abstract: [1] Ground-based observations with a Fourier transform spectrometer in the infrared region (FTIR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…They include ozone data for the lower layer of the atmosphere beginning in 2005. We performed a comparison of these ozone profiles for Kiev and the profiles recovered by us from the infrared Fourier spectrometer observations and modelling with MODTRAN4 code [7,8,9]. The first comparison of our retrieved profile for April 23, 2007 with OMO3PR data showed a significant difference in tropospheric part of the profiles (Fig.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…They include ozone data for the lower layer of the atmosphere beginning in 2005. We performed a comparison of these ozone profiles for Kiev and the profiles recovered by us from the infrared Fourier spectrometer observations and modelling with MODTRAN4 code [7,8,9]. The first comparison of our retrieved profile for April 23, 2007 with OMO3PR data showed a significant difference in tropospheric part of the profiles (Fig.…”
Section: Methodsmentioning
confidence: 98%
“…Simulation of ground-level ozone concentrations in Kiev for an episode of its high concentration in August 2000 [3,10,11] is performed using a model of urban air pollution UAM-V [12]. Aa study of total ozone over Kiev and its concentration changes with altitude in the troposphere was also carried out using ground-based observations with the infrared Fourier spectrometer at the Main Astronomical Observatory of the National Academy of Sciences of Ukraine (MAO NASU) as a part of the ESA-NIVR-KNMI project no 2907 "OMI validation by ground based remote sensing: ozone columns and atmospheric profiles (2005)(2006)(2007)(2008))" [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Ground-based observations of strong and weak absorption lines in the electromagnetic spectrum of direct solar radiation transmitted through the Earth's atmosphere to the surface are routinely made at the Main Astronomical Observatory of National Academy of Sciences Ukraine with the Fourier Transform InfraRed spectrometer (FTIR model Infralum FT 801, [Egevskaya, Vlasov, Bublikov, 2001]). This particular instrument was optically redesigned for the study of atmosphere pollution in the Kiev metropolitan area [Shavrina et al, 2007]. The working spectral range of the Fourier spectrometer is 2-12 microns (equivalent to 800-5000 cm −1 with a best spectral resolution of˜1.0cm −1 .…”
Section: Ground Based Ftir Ozone Observationsmentioning
confidence: 99%
“…For the analysis of our observations of 2007-2008, we used MLS data version v2.2, the higher accuracy of which has enabled us to develop a new method of ozone profile analysis: we are now varying the input profile of the tropospheric ozone only, where we only scale the stratospheric profile by a certain factor within the specified accuracy of MLS (2-5% in the layers of the pressure 216-0.02 hPa) without modifying its overall shape. A detailed description of our method for determining detailed tropospheric and stratospheric concentrations of ozone can be found in [Shavrina et al, 2007, Shavrina et al, 2008. The result of the analysis is the best fit of the model spectrum to the observed spectra of the ozone band, from which we obtained the best estimates of the tropospheric vertical profiles of ozone, the total column amount of ozone in the troposphere and finally the total column amount of ozone in the atmosphere.…”
Section: Spectral Modeling and Analysismentioning
confidence: 99%
“…An asterisk indicates that the paper is in the first publication group (about 20 papers); those papers without an asterisk are in the second and third groups. Other than the grouping by instrument and constituent, the order has no other Kovalenko et al [2007] BrO validation Froidevaux et al [2008b] HCl validation Lary and Aulov [2008] HCl comparisons with ACE and HALOE HCl measurements Wu et al [2008] ice water content validation Schwartz et al [2008] temperature and geopotential height validation Manney et al [2007] comparison of O 3 , N 2 O, H 2 O, HNO 3 and HCl with solar occultation data Considine et al [2008] comparison of MLS and HALOE data products using noncoincident Lagrangian methods Kroon et al [2008a] comparison of the OMI-TOMS and OMI-DOAS data products McPeters et al [2008] validation of column ozone Shavrina et al [2007]* validation of column ozone in Kiev Kroon et al [2008b] ozone column compared to CAFS Balis et al [2007]* ozone column, OMI TOMS and DOAS comparisons Migliorini et al [2008] comparison of total column ozone with assimilation Kramer et al [2008] total Bucsela et al [2008] NO 2 comparison of aircraft with NRT and standard data products Brinksma et al [2008] NO 2 validation using data from the DANDELIONS campaign Boersma et al [2008] NO 2 OMI and SCIAMACHY comparisons Ionov et al [2008] NO 2 validation from ground-based instruments Wenig et al [2008] NO 2 validation from direct Sun Brewer measurements Vasilkov et al [2008] Raman cloud pressure validation Sneep et al [2008] cloud CO validation using AVE measurements Eldering et al [2008] cloud top pressure and optical depth retrievals Osterman et al [2008] validation of ozone profiles and columns Nassar et al [2008] comparison of TES ozone profiles and sondes Richards et al [2008] ozone profile validation using INTEX-B aircraft measurements Shephard et al [2008a] water vapor validation Shephard et al [2008b] radiance comparisons with S-HIS and AIRS Overview papers are indicated by crosses. Papers published in the first group of the special section are indicated by asterisks, and papers in the second and third ...…”
Section: Aura Validationmentioning
confidence: 99%